SIGNIFIKANSI SHALAT DALAM MEMBENTUK KETEGUHAN JIWA: KAJIAN PSIKOLOGIS METODOLOGIS TAZKIYATUN NAFS - Rafliyanto, Muhammad (Universitas Islam Negeri Syekh Ali Hasan Ahmad Addary Padangsidimpuan, 2025)
This research aims to examine the significance of prayer in shaping spiritual steadfastness through a psychological approach and tazkiyatun nafs methodology. Prayer, as a fundamental act of worship in Islam, not only has a ritual dimension but is also an integral means of spiritual development. From the perspective of tazkiyatun nafs, prayer functions as an ongoing process of spiritual purification to achieve inner stability and strength. This study employs a qualitative-descriptive method with a literature review approach, examining classical and contemporary literature related to tazkiyatun nafs, Islamic psychology, and the spiritual meaning of prayer. The findings indicate that performing prayer with devotion and consistency can strengthen individual psychological aspects such as inner peace, resilience to life’s pressures, and self-control. These findings affirm that prayer is not merely a spiritual obligation but an effective means in fostering mental resilience, as depicted in various verses of the Quran and the analyses of classical tazkiyah scholars such as Al-Ghazali and Ibn Qayyim al-Jauziyah. The implications of this research recommend the integration of prayer values into mental and spiritual strengthening programs in various educational and mental rehabilitation institutions.